BACTERIAL PATTERN AMONG SEPSIS PATIENTS IN INTERNAL MEDICINE INPATIENT WARD DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Ilma Dzurriyyatan Toyyibah; Musofa Rusli; Juniastuti Juniastuti (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlights:1. Bacteria remain a major cause of bacterial sepsis.2. The most common causal agent in bacterial septicaemia was the gram-positive bacterium. Abstract: Background: Bacteria remain the primary cause of bacterial sepsis. Gram-negative bacteria are the most commonly isolated from sepsis patients. However, gram-positive bacterial infections have also increased recently. Objective: To identify the pattern of bacterial infection in sepsis patients in Internal Medicine inpatient ward Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Material and Method: This retrospective study reviewed the medical records of all sepsis patients in Internal Medicine Ward Dr. Soetomo General Academic Hospital, Surabaya, Indonesia from January 1 – December 31, 2016. All patients were divided according to bacterial species into two groups: patients with gram-positive and gram-negative infection. The collected data were statistically analyzed using SPSS ver. 16.0 to find out the frequency. Result: From 179 eligible data reviewed, there were 103 (57.5%) patients with gram-positive bacterial infection and 76 (43.5%) patients with a gram-negative bacterial infection. The major isolates of gram-positive bacteria were Staphylococcus hominins (30 isolates) and gram-negative bacteria was Escherichia coli (30 isolates), 43 isolates showed multi-drug resistant organisms; Escherichia coli ESBL 23 isolates, Klebsiella pneumoniae ESBL 3 isolates, Klebsiella oxytoca ESBL 2 isolates and Methilcillin Resistance Staphylococcus aureus 5 isolates. Conclusion: The most common causative agent in bacterial sepsis was gram-positive bacteria. The major isolated gram-positive bacteria are Staphylococcus hominis and gram-negative bacteria were Escherichia coli. The species of multi-drug resistant organisms found are Methilcillin-Resistant Staphylococcus aureus (MRSA), Escherichia coli ESBL, Klebsiella pneumonia ESBL and Klebsiella oxytoca ESBL. Among the patients with multi-drug resistant organism infection, Escherichia coli ESBL were the most prevalent one.